Assessment of Drug Adherence and Adverse Effects of Disease-Modifying Antirheumatic Drugs (DMARDs) in Patients of Rheumatoid Arthritis Attending a Tertiary Care Hospital in India - Patel, Tejal C.; Pandit, Prasad R.; Doshi, Zankrut R.; Londhe, Vikram A. (Universitas Padjadjaran, Indonesia, 2023)
Adherence to drug treatment is one of the key factors in treating chronic diseases like rheumatoid arthritis (RA) to maintain remission and prevent functional disability. Poor medication adherence is directly associated with a worse prognosis and an increase in healthcare utilization, adding to a financial burden. Hence, the present study was proposed to assess drug adherence in diagnosed patients of RA attending a tertiary care hospital. The study was initiated after obtaining institutional ethics committee permission, and written informed consent was requested from all the eligible patients before their enrolment. This cross-sectional questionnaire based study was conducted on RA patients attending the rheumatology outpatient department. The patient’s adherence to the drugs prescribed was assessed using the 19-item Compliance Questionnaire Rheumatology (CQR), and the correlation betweendrug adherencewithvariousdemographic,disease,andmedication-relatedvariableswasstudied. After screening 103 patients, 75 patients fulfilling the selection criteria were enrolled, and theirdatawasanalyzed. The adherence measured using the CQR score was in therange of 54.39% to 68.42%, with a mean CQR score of 62.27 ± 2.76.Anegative correlation was found between the CQR score and the number of ADRs (r=-0.12,p>0.05) and age (r=-0.06, p>0.05). A positive correlation was found between the CQR score and variables like sex, education, and number of medications, but none were statistically significant. Unsatisfactory compliance was evident in the present study. Therefore, integrating drug treatment with strategies to improve patient adherence may improve clinical outcomes and quality of life, reducing healthcare costs.